2013
DOI: 10.1007/s00253-013-5423-7
|View full text |Cite
|
Sign up to set email alerts
|

Genomic structural variations contribute to trait improvement during whole-genome shuffling of yeast

Abstract: Whole-genome shuffling (WGS) is a powerful technology of improving the complex traits of many microorganisms. However, the molecular mechanisms underlying the altered phenotypes in isolates were less clarified. Isolates with significantly enhanced stress tolerance and ethanol titer under very-high-gravity conditions were obtained after WGS of the bioethanol Saccharomyces cerevisiae strain ZTW1. Karyotype analysis and RT-qPCR showed that chromosomal rearrangement occurred frequently in genome shuffling. Thus, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Firstly, it is possible to carry out a prescreening by subjecting the hybrid population to a severe stress by plating the cells on medium that contains for instance high ethanol or acetic acid levels, conditions encountered during fermentation. Next, only fast-growing colonies are tested individually in small-scale fermentations, and only superior hybrids are used for a next round of shuffling (Shi et al ., 2009; Zheng et al ., 2011ab, 2013ab; Tao et al ., 2012). Other investigators have instead tried to first improve stress tolerance and found that hybrids generated after multiple rounds of genome shuffling and selection also showed increased general fermentation performance (Wei et al ., 2008; Cao et al ., 2009, 2010, 2012; Hou, 2009; Wang & Hou, 2010; Jingping et al ., 2012; Lu et al ., 2012; Wang et al ., 2012a).…”
Section: Natural and Artificial Diversitymentioning
confidence: 99%
“…Firstly, it is possible to carry out a prescreening by subjecting the hybrid population to a severe stress by plating the cells on medium that contains for instance high ethanol or acetic acid levels, conditions encountered during fermentation. Next, only fast-growing colonies are tested individually in small-scale fermentations, and only superior hybrids are used for a next round of shuffling (Shi et al ., 2009; Zheng et al ., 2011ab, 2013ab; Tao et al ., 2012). Other investigators have instead tried to first improve stress tolerance and found that hybrids generated after multiple rounds of genome shuffling and selection also showed increased general fermentation performance (Wei et al ., 2008; Cao et al ., 2009, 2010, 2012; Hou, 2009; Wang & Hou, 2010; Jingping et al ., 2012; Lu et al ., 2012; Wang et al ., 2012a).…”
Section: Natural and Artificial Diversitymentioning
confidence: 99%
“…cerevisiae strains used in dough leavening, bioethanol production, ale-type beer fermentation, and distilled-beverage production. In these strains, aneuploidy typically involves small deviations in copy number of one or a few chromosomes (117119). Since accurate information is available for only a few of the many hundreds of such strains stored in culture collections, the incidence of CCNV may well be underestimated.…”
Section: Ccnv In Industrial Saccharomyces Yeastsmentioning
confidence: 99%
“…Use of the mitotic inhibitor methyl benzimidazole-2-yl-carbamate (MBC) to mutagenize the aneuploid bioethanol strain ZTW1 demonstrates the potential of this approach (153). Treatment of strain ZTW1 with MBC yielded strains with an improved fermentative capacity under industrial high-gravity conditions (119), enhanced viability after drying (154), and higher final ethanol titer (124). These observations and the frequent appearance of CCNV in ALE suggest that such interference with chromosome segregation may deserve reconsideration in industrial yeast strain improvement.…”
Section: Outlook: Understanding and Engineering Ccnv In Industrial Comentioning
confidence: 99%
“…Some researchers used laboratory strains [10,11], which likely do not perform well under industrial conditions. In other studies, the novel hybrids were not tested on a pilot scale [12-15]. Moreover, genome shuffling is often combined with genetic engineering [16,17], making some industrial applications problematic.…”
Section: Introductionmentioning
confidence: 99%